Editorial: Social Entrepreneurship and Digitalization - Orero-Blat, Maria (2025)
This editorial introduces the special issue of TEC Empresarial dedicated to exploring the nexus between social entrepreneurship and digitalization. Social entrepreneurship, characterized by its dual mission of social impact and economic sustainability, is increasingly shaped by digital transformation. Digital technologies—ranging from crowdfunding platforms to mobile applications—enable social ventures to mobilize resources, expand their reach, and enhance inclusivity. The editorial synthesizes contributions that address critical aspects related to alternative financing through crowdfunding, digital inclusion of marginalized populations, and the role of education and local ecosystems in fostering social entrepreneurial. The contributions included in the special issue emphasize how digital tools can catalyze empowerment, particularly among women and older adults, while also identifying persistent barriers related to gender and institutional support. The collection advocates for interdisciplinary research that integrates perspectives from ethics, gender studies, and organizational behavior, and calls for participatory approaches to co-develop digital solutions with different stakeholders. By employing diverse methodological to analyze different regional contexts, this issue contributes to a deeper understanding of how digital innovation can contribute to inclusive and sustainable social change.